2017
DOI: 10.3390/molecules23010062
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of a Novel Cold-Water-Soluble Polysaccharide from Astragalus membranaceus and Its Antitumor and Immunological Activities

Abstract: The polysaccharides of Astragalus membranaceus have received extensive study and attention, but there have been few reports on the extraction of these polysaccharides using cold water (4 °C). In this study, we fractionated a novel cold-water-soluble polysaccharide (cAMPs-1A) from Astragalus membranaceus with a 92.00% carbohydrate content using a DEAE-cellulose 52 anion exchange column and a Sephadex G-100 column. Our UV, Fourier-transform infrared spectroscopy (FTIR), high-performance gel permeation chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 51 publications
(52 reference statements)
1
41
0
Order By: Relevance
“…In particular, nobiletin is abundant in the flavedos of Acrumen species, such as Dancy tangerine ( C. tangerina ) and Ponkan mandarin ( C. reticulata ). Recently, the identification and functional characterization of OMTs have been reported in several plants species 4 , 31 , 32 . However, studies on OMTs in citrus fruits are still limited, and the nobiletin biosynthetic pathway in citrus remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nobiletin is abundant in the flavedos of Acrumen species, such as Dancy tangerine ( C. tangerina ) and Ponkan mandarin ( C. reticulata ). Recently, the identification and functional characterization of OMTs have been reported in several plants species 4 , 31 , 32 . However, studies on OMTs in citrus fruits are still limited, and the nobiletin biosynthetic pathway in citrus remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a polysaccharide from N. commune is able to suppress proliferation of MCF-7 cells via modulation of endoplasmic reticulum stress, which is known to trigger unfolded protein response and lead to cell death [ 53 ]. Also, a number of studies have shown that the anti-tumor activity of polysaccharides is closely associated with their regulatory effects on immune system [ 54 , 55 ], and, intriguingly, N. commune polysaccharide has been previously shown to activate the complement system [ 2 ], an important part of the immune system acting to enhance the adaptive immune response. Therefore, other mechanisms are also likely to contribute to the inhibitory effect of nostoglycan and other Nostoc polysaccharides on the proliferation of tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Phagocytosis of peritoneal macrophages was measured referred to in references with minor modification (Chen, Zhang, Shen, & Wang, 2010;Liu et al, 2017). 5 mL saline was injected to abdominal cavity of each mouse.…”
Section: Macrophage Phagocytosis Assaymentioning
confidence: 99%